(untitled) (International Journal of Engineering and Computer Science, 2015)
Document binarization has the purpose to decrease the quantity of information present in the document and to watch out only appropriate data which permits applying document analysis depending on binarization algorithm. From the survey, it has been originate that not any of the existing technique gave proficient results in document binarization. So, to determine this matter, a new algorithm for recuperating degraded document has been proposed. The proposed technique consists of three parts. The first part has the accountability to pertain the Decision based switching median filter image filter to smooth and restore a degraded document. The second part applies adaptive image contrast enhancement to text and background variation caused by different types of document degradations followed by actual binarization. The algorithm has been designed and implemented in MATLAB using image processing toolbox. The comparative analysis has shown the improvement in results of proposed algorithm on the basis of various performance metrics.